Hydroelectric power generator using vertical axis turbine with adaptive blades - Rizki Nurilyas Ahmad; Soraya Komala Firdaus; Mohammad Nasrul Mubin; Hasyim Asy'ari; Tindyo Prasetyo; Iqbal Reza Pradana (International Journal of Applied Power Engineering (IJAPE), 2026)
The implementation of micro-hydro power plants (MHPPs) offers a strategic solution for achieving energy independence, particularly within remote communities. This study proposes the development of a hydroelectric power generator with a vertical axis turbine, designed not only as a source of clean energy but also to minimize visual pollution. The system maximizes submerged components, thereby reducing its visual impact. Although MHPPs technology is widely applied to address electrification challenges in remote areas, the system proposed in this study, with its components predominantly submerged below the water surface, offers a visually unobtrusive solution that is also well-suited for urban environments. However, conventional locked-blade turbines often experience significant efficiency losses due to counter-flow pressure acting on blades moving against the water stream, highlighting the need for an adaptive mechanism to minimize drag and optimize energy capture. The hydroelectric power generator using vertical axis turbine with adaptive blades consistently demonstrated better performance than a system using locked blades. The adaptive-blade configuration outperformed the locked-blade system, exhibiting a 5.1% increase in average turbine efficiency and a 3.5% improvement in overall system efficiency.